USE OF AGENCY FEES FOR UNION’S POLITICAL CAUSES: DOES OUR LAW ADEQUATELY PROTECT RIGHTS OF NON-MEMBERS OF A REPRESENTATIVE TRADE UNION AGAINST ITS UNSCRUPULOUS USE OF AGENCY FEES FOR POLITICAL IDEALS? - Daniel Phiri Mulaudzi (Obiter, 2024)
The inclusion of a fundamental right to conclude agency-shop agreements in section 23(6) of the Constitution of the Republic of South Africa, 1996 (Constitution) places beyond dispute the issue regarding the constitutionality of such agreements. This is in recognition of the crucial role that agency shops play in facilitating collective bargaining, which is fundamental to advancing peace in the workplace. This legitimate and worthwhile purpose justifies the limitation (in accordance with section 36 of the Constitution) of non-members’ right to freedom of association.The essence of this note is an examination of the legislature’s failure to adequately regulate a union’s use of agency fees for political activities under section 25 of the LRA. The key object is to demonstrate that South Africa’s failure to regulate the use of agency fees for political activities undermines the reformed labour law’s intention to protect the constitutional rights of workers. It argues that this ideal is compromised when, owing to such omission, unions can use agency fees for political activities under section 25(3)(d) without regulation.